Mental Accounting, Loss Aversion, and Tax Evasion: Theory and Evidence - Sanjit Dhami; Narges Hajimoladarvish (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The evidence shows source-dependent entitlement to income sources and individuals are reluctant to part with income they feel more entitled to, e.g., earned labor income. Taxpayers may also be more reluctant to part with tax payments (evade more) from income sources they feel more entitled to- a form of mental accounting. We embed two main hypotheses within a rigorous theoretical model based on prospect theory. From incomes sources they feel more entitled to, taxpayers experience (i) greater loss aversion from paying taxes, and (ii) lower moral costs of evasion. We confirm the predictions of our model through MTurk experiments. Evasion is increasing in the tax rate and decreasing in the audit penalty. Moral costs influence taxpayers' decisions. Loss aversion, measured "directly" for the first time for each individual in an evasion experiment, reduces evasion, as predicted by our theory. Loss aversion, risk aversion, and their interaction, are critical determinants of evasion.
Keywords: C91; C92; D82; D91; G21; 330; mental accounting; tax evasion; loss aversion; morality; prospect theory; risk-aversion